Gilbert's syndrome revisited - Vítek, Libor; Tiribelli, Claudio (Journal of hepatology, 2023)
Gilbert's syndrome, also known as benign hyperbilirubinaemia, was described more than 100 years ago. It has usually been considered a physiological abnormality characterised by a mild elevation of the systemic level of unconjugated bilirubin, in the absence of any underlying liver or overt haemolytic disease. However, since the re-discovery of the potent antioxidant effects of bilirubin in the late 1980s, as well as multiple intracellular signalling pathways affected by bilirubin, an ever-increasing body of evidence suggests that individuals with Gilbert's syndrome may benefit from the mild hyperbilirubinaemia and are actually protected from the development of a wide variety of "diseases of civilisation" such as cardiovascular diseases, certain cancers, and autoimmune or neurodegenerative diseases. This review analyses the current state of medical knowledge given recent discoveries in this rapidly developing field, as well as their possible clinical significance, and provides a new perspective on this condition.
Keywords: Hyperbilirubinemia; benign hyperbilirubinemia; antioxidancia; hyperbilirubinemie; Gilbertova nemoc; Bilirubin; Gilbert’s syndrome; Liver; bilirubin; lidé; játra; Antioxidants; civilization diseases; Humans; Gilbert Disease